Sincronização de oscilação magnética com processos de soldagem a arco - Larquer, Thiago Resende (2015)
Currently the search for improvements in processes and mechanized/automated welding techniques has been intense due to the skilled labor shortage. In this line, the combination of processes and even operational modes (polarity and/or metal transfer mode) within a process, in addition to the possibility of combining welding current levels, has gained attention. Through operational modes and/or current levels, the arc energy (both thermal and kinetic) delivered to the workpiece can be changed. By combining this feature with the arc motion, the arc energy can be optimally distributed to control the formation of the weld bead. A relatively simple way to control the arc motion is by magnetic oscillation - deflection of the electric arc by an electromagnet. Thus, this work exploits the synchronization between the arc oscillation and the welding process to control the arc energy distribution on the workpiece. To this end, a synchronized oscillation system, including hardware and software, was devised to enable to control the magnetic oscillation and a multiprocess welding power source synchronously. Then, a characterization of the magnetic arc deflection was carried out (according to the electromagnet voltage, welding current and arc length) based on high-speed filming. In order to exploit the synchronized magnetic oscillation technique with different welding processes, two approaches were executed, both with arc oscillation transverse to the welding direction, and then compared to reference conditions (welding without oscillation and with unsynchronized oscillation). The TIG process was synchronized to the magnetic oscillation varying the level of welding current according to the arc position, being the effect on the control of the weld beads width the basis for analysis. The MIG/MAG process was synchronized to the magnetic oscillation with different welding operational modes according to the arc position, being the effect on the control of the molten zone geometry the basis for evaluation. The synchronized oscillation system was able to control the formation of the weld beads for the TIG as well as for the MIG/MAG welding. In the case of the synchronized TIG, it was possible to increase the weld bead width on the side with higher current and lateral stop time and vice versa. In the case of the synchronized MIG/MAG, it was possible to control the molten zone geometry, besides reduce the dilution of the resulting beads, with little variation in the top reinforcement and at the same time with increasing in the bead widths and with tendency for more side penetration. It is believed that the magnetic oscillation technique synchronized with the welding processes can be exploited in several applications, where it is important to optimize the arc energy distribution on the workpiece.